Software Applications for the Social Inclusion of People with Disabilities: A Review of the Scientific Literature of the last 10 years (LACCEI, 2024)
The present systematic review aimed to analyze how software applications contribute to social inclusion contemplating the type of disability, the role and the global context in the research of the last ten years. A systematic review of research was carried out considering an information collection procedure based on the inclusion and exclusion criteria, with the adaptation of the PRISMA methodology. The selection of investigations obtained 118 results for meeting the established criteria. The disabilities with the highest contribution in software were hearing impairment (23%) and visual impairment (23%) while autism (7%) and Down syndrome (7%) were the disabilities with the least attention. Among the countries that have offered the largest contribution, Ecuador stands out (32%), followed by Colombia (17%) and Mexico (16%). The function of the software that stands out is the educational context (51%) and inclusive technology software (27%), with medical diagnosis and treatment software (12%) and software for work and daily life (10%) being the lowest contributions.